Mesenchymal stromal cells highly expressing Sca-1 promote breast cancer lung metastasis through recruiting myeloid cells - Lijuan Cao; Yanan Li; Minghui Ou; Artem Smirnov; Rui Liu; Tingting Wang; Xiao Su; Peishan Li; Mancini Mara; Eleonora Candi; Zhiyuan Zheng; Gerry Melino; et al. (Cell Death and Disease)
Abstract Mesenchymal stem/stromal cells (MSCs) are integral components of the tumor microenvironment and critical for the colonization of disseminated cancer cells; specifically, stem cell antigen (Sca-1) is recognized as a surface marker of MSCs. In this study, we found that MSCs highly expressing Sca-1 are positively associated with lung metastasis. MSCs derived from the lungs of mice bearing metastasized breast tumors (LMSCs) exhibited higher level of Sca-1 compared to those with adenoma. When co-injected with 4T1 cells intravenously, Sca-1high LMSCs resulted in more tumor nodules in lung tissue than Sca-1low LMSCs. Furthermore, Sca-1high LMSCs expressed higher levels of CCL2, CCL7, and CXCL1 than Sca-1low LMSCs. Sca-1high LMSCs can directly recruit 4T1 cells through producing CXCL1. Additionally, Sca-1high LMSCs are highly potent in recruiting immune cells of the myeloid lineage (neutrophils and macrophages) to the lungs. Inhibition of macrophage chemotaxis by Bindarit, an inhibitor of CCL2/7/8 transcription, decreased the lung tumor burden induced by Sca-1high MSCs. Using Ccr5 −/− mice, it was further confirmed that Sca-1high LMSCs promote tumorigenesis by recruiting macrophages, further supporting that the increased recruitment of macrophages mediates the pro-metastasis effect of Sca-1high LMSCs. Collectively, this study demonstrated that Sca-1high LMSCs and their effectors could be targeted to inhibit breast cancer metastasis to the lung.